Examining Massive Digital Libraries (MDLs) and Their Impact on Reference Services. Issue 4 (1st October 2016) - Weiss, Andrew
ABSTRACT: Massive Digital Libraries such as Google Books and the HathiTrust can provide libraries with virtual ready-reference collections that match the scope of print collections. Their impact reaches into the tens of millions of public domain and copyrighted titles. Yet, problems persist with these digitized book collections. This article examines some of the flaws and unintended consequences of relying on Massive Digital Libraries at the expense of local print collections. Such problems include lack of metadata accuracy, poorly implemented optical character recognition, lack of quality control in the mass-digitization process, the problem of linguistic representation, and the lack of subject diversity in the source collections.